Efficient Enhancement of Electron Transport and Collection Capability in PTB7:PC71BM‐based Solar Cells Enabled by Sulforhodamine Cathode Interlayers. Issue 9 (14th March 2019) - Song, Wei; Li, Wang; Peng, Ruixiang; Fanady, Billy; Huang, Jiaming; Zhu, Wenqing; Xie, Lingchao; Lei, Tao; Ge, Ziyi
Abstract: Development of low‐cost water‐/alcohol‐soluble interfacial materials is a crucial issue to promote the commercialization of polymer solar cells (PSCs). Herein, two derivatives of low‐cost rhodamine, called sulforhodamine 101 (SR101) and sulforhodamine B (SRB), are applied as cathode interfacial layers (CILs) to effectively improve the charge‐carrier transportation and collection, reduce the work function (WF) of Al counter electrode, and decrease the series resistance and charge recombination in the PSCs. As a result, SR101‐based devices show excellent performance with the highest power conversion efficiency (PCE) of 9.10 %, superior to that of both the control devices with MeOH/Al and Ca/Al. Notably, sulforhodamine is commercially available with low cost and great solution‐processability. This work demonstrates that sulforhodamine has a great potential as a CIL material, which is suitable for the large‐area fabrication process and commercialization of highly efficient PSCs. Abstract : Polymer Solar Cells 101 : Highly efficient polymer solar cells were achieved by employing sulforhodamine as a cathode interfacial layer. The conjugated functional groups with positive and negative charges of SR101 can provide good interfacial modification abilities in electron transport and collection. The results demonstrate that the best device with PTB7:PC71 BM show an inspiring PCE of 9.10 %, which is superior to that of the control devices.